Enhancing inclusive Education through Audio books: A Collaborative Approach for Visually Impaired Children (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In our modern world, people from all walks of life and all demographics agree that education is crucial. In today's knowledge-driven society, everyone needs access to high-quality education if they want to thrive Even more concerning is the fact that many visually impaired kids have a hard time with not just understanding academic topics but also finishing their work and doing well on tests. Recently developed audio-based assistive solutions for the visually impaired are included with regard to research on mobile assistive technology and applications for visually impaired people. Audiobooks gained popularity as a viable alternative to Braille books due to their portability. Adding music and sound effects made the audio books more visually appealing, which helped them reach all children, even those with disabilities.